Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Menggunakan Model Pembelajaran Index Card Match Di Kelas X MAN 1 Padang Lawas - Azhari Hasibuan, Sundut; Safitri Lubis, Irna; Pramudia Fadli, Veri; Sitanggang, Kholidah (Journal of Information System and Education Development, 2025)
This study aims to improve the mathematical problem solving skills of students in class X MIA-4 MAN 1 Padang Lawas by using the Index Card Match learning model. This type of research is a class action research conducted in 2 cycles, each cycle consists of 2 meetings. The subjects of this study were students of class X MIA-4 MAN 1 Padang Lawas in the 2024/2025 school year totaling 28 students. Based on the results of the mathematical problem solving ability test given to students, the number of students who completed the initial observation was 6 people, cycle I was 19 people, and cycle II was 25 out of 28 students. While the percentage of classical completeness in pre-research was 21.43%, cycle I was 67.85%, and cycle II was 89.29%. The increase in the percentage of classical completeness was 67.86%, from 21.43% to 89.29%. In addition, each indicator of students' mathematical problem solving ability increased in each cycle. The increase in the percentage of mastery of the indicator of problem solving ability that best understands the problem is 87.85%. While the lowest percentage of mastery of problem solving ability indicators is checking back, which is 77.14%. Based on the results of this study, it can be concluded that the Index Card Match learning model can improve the mathematical problem solving skills of students in class X MIA-4 MAN 1 Padang Lawas